2021
DOI: 10.25008/jkiski.v6i1.525
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behavior as a Potential Acceptance of Renewable Energy Source in Indonesia

Abstract: The trend of using renewable energy (RE) as a substitute for fossil energy is increasing as the issue of global warming continues to be echoed. Previous studies about RE focusing much on the availability and infrastructure of RE, yet no study about potential acceptance of RE in Indonesia has been conducted. Therefore, this study will fill the gap in the topic of RE consumer behavior. Qualitative approach was used in this study, by conducting literature reviews to relevant studies about consumer behavior toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Several literature studies have been conducted to analyze and determine the factors that may affect consumers' use of renewable energies or their complete switch to them. The studies by Avicenna and Febriani [20] and Sardianou and Genoudi [21] found that consumers' education level affects their acceptance of renewable energy. Consumers with a broader knowledge of the benefits of renewable energy and the adverse effects of fossil-fueled energy sources tend to have a higher acceptance rate than those without such knowledge [22,23].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Several literature studies have been conducted to analyze and determine the factors that may affect consumers' use of renewable energies or their complete switch to them. The studies by Avicenna and Febriani [20] and Sardianou and Genoudi [21] found that consumers' education level affects their acceptance of renewable energy. Consumers with a broader knowledge of the benefits of renewable energy and the adverse effects of fossil-fueled energy sources tend to have a higher acceptance rate than those without such knowledge [22,23].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Specific public policies on Energy Systems Integration (ESI) have also emerged to regulate energy use and regulation. However, it turns out that this policy creates economic obstacles in Europe where policies related to ESI cannot increase the number of investors who invest in ESI (Cambini et al, 2020) The decision to consume renewable energy in Europe is different from that in Asia, especially Indonesia. Each region in Indonesia implements public policies based on a decentralized or devolved system and a centralized system.…”
Section: The Effect Of Renewable Energy Consumption Decisions Of Rura...mentioning
confidence: 99%
“…Salah satu referensi penelitian yang digunakan oleh peneliti adalah "Consumer Behavior as a Potential Acceptance of Renewable Energy Source in Indonesia" (Avicenna & Febriani, 2021). Penelitian tersebut menggunakan pendekatan kualitatif, dengan melakukan kajian literatur terhadap studi-studi yang relevan tentang perilaku konsumen terhadap pemanfaatan energi terbarukan di berbagai negara.…”
Section: Latar Belakangunclassified